Common Ictal and Interictal Perfusion Patterns: A Window into the Epileptogenic Network and SUDEP Mechanism in Drug-Resistant Focal Epilepsy - Chacón, Lilia M. M.; García, Lidice Galan; García-Ramón, Karla Batista; Báez Martin, Margarita Minou; Bosch-Bayard, Jorge; Alfonso, Maydelis Alfonso; Batista, Sheyla Berrillo; Bermudez, Tania de l. P.; González, Judith González; Coroneaux, Abel Sánchez; Ruiz, Ángel Águila; Roque, Marlene Perera; et al. (Current Pharmaceutical Design, 2022)
Background: Focal epilepsies have been described as a network disease. Noninvasive investigative techniques have been used to characterize epileptogenic networks. Objective: This study aimed to describe ictal and interictal cortical and subcortical perfusion patterns using single- photon emission computed tomography (SPECT) in patients with drug-resistant epilepsy (DRE). Methods: Thirty-five interictal-ictal SPECT scans were obtained from 15 patients with DRE. A methodology was developed to get a relative perfusion index (PI) of 74 cortical and sub-cortical brain structures. K-means algorithm, together with modified v-fold cross-validation, was used to identify the two regions of interest (ROIs) that represent hypoperfused and hyperperfused areas. Results: In common with the individual analysis, the statistical analysis evidenced that the hyperperfusion ROIs resulting from group analysis during interictal and ictal involved mainly the cingulate gyrus, cuneus, lingual gyrus, and gyrus rectus as well as the putamen. ROIs hypoperfused included the red nucleus, the substantia nigra, and the medulla. The medians of the group analysis of the hypoperfusion and hyperperfusion ROIs were 0.601-0.565 and 1.133-1.119 for the ictal and interictal states, correspondingly. A group of mostly cortical structures involved in the hyperperfused ROIs in both interictal and ictal states showed no change or negative change in the transition from interictal to ictal state (mean change of -0.002). On the other hand, the brain stem, basal ganglia, red nucleus, and thalamus revealed a mean global change of 0.19, indicating a mild increase in the PI. However, some of these structures (red nucleus, substantia nigra, and medulla oblongata) remained hypoperfused during the interictal to ictal transition. Conclusion: The methodology employed made it possible to identify common cortical and subcortical perfusion patterns not directly linked to epileptogenicity, for a better epileptogenic network and sudden unexpected death (SUDEP) mechanism in DRE.
Keywords: ictal SPECT